Peri-implant soft tissue augmentation with a porcine collagen matrix. - Yuri Castro; Silvana Grados; Sixto Grados (Universidad de Concepción., 2014)
A good amount and width of keratinized tissue around implants has been associated with better peri-implant health, less bone loss and improved esthetics. The purpose of this case was to evaluate a new porcine xenograft (collagen matrix) used as an interpositional graft to augment thickness of the peri-implant mucosa. There are few studies using a collagen matrix as a substitute for subepithelial connective graft around implants. This case involved a clinical implant in teeth 15 in which it was made the most of it during placement of healing abutment by taking the opportunity to increase periimplant mucosa with a collagen matrix. Thickness increased 1.5mm while the amount of keratinized mucosa was kept at 4mm. It is concluded that the collagen matrix of porcine origin is a good alternative to increase thickness of the peri-implant mucosa and reduce morbidity. It is easy to handle and suture as well.